Lacrimal canaliculus laceration in a reference center in the Center-West of the state of São Paulo - Almeida, Alice Carvalho Gouveia de [UNESP] (2024)
Objective: To describe the clinical and epidemiological characteristics, surgical techniques, and results of the canalicular laceration treatment at our service. Methods: A retrospective study was carried out from January 2012 to June 2020, considering canalicular injuries operated at a reference center. Demographic data, lesion characteristics, surgical details, and treatment outcomes were obtained from electronic medical records and were statistically analyzed. Results: Twenty-six cases of people with canalicular lesions aged between 2 to 71 years old were included, of whom 73.1% were men. The superior canaliculus was affected in 53.9%; 80.8% of patients searched for care within the first 24 hours, and 46.2% had the surgery performed between 24-72 hours after trauma. All patients had mono or bicanalicular intubation and the time elapsed between surgery and silicone removal ranged from 0 to 183 days. After surgery, 21 patients (80.8%, p<0.05) did not present any complications, two (7.7%) evolved with canalicular obstruction, two (7.7%) with granuloma, and one (3.8 %) with lacrimal puncta ectropion. Conclusion: In our practice, canalicular injuries are more common in children or young men, affecting mainly the superior canaliculus, and treatment success using our approach can be achieved in most of the cases. However, great controversies remain on the subject, such as type of intubation and when to remove the silicone tube from the lacrimal pathway. Larger series are required to consolidate controversial concepts.